2022
DOI: 10.17323/jle.2022.12467
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Technology Acceptance Model (TAM) towards ICT Use for English Language Learning

Abstract: Background. The use of ICT in learning English can assist learners to improve their language skills, aside from empowering and motivating them in English language learning. ICT utilization can provide opportunities for collaboration and interaction in the learning process. Purpose. The present study was conducted to examine the motivation, ICT skills, equipment, and attitudes factors towards the use of ICT tools for English learning in English as a Foreign Language (EFL) context. Methods. The quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Furthermore, attitude was found to be a significant predictor of students' actual usage of e-learning in English learning. This result is consistent with those of previous research on technology acceptance in language learning (Alfadda and Mahdi, 2021;Rafiee and Naghneh, 2021;Arif et al, 2022;Sulistiyo et al, 2022), demonstrating that factors of the technology acceptance model are the main factors influencing students' adoption of technology for language learning.…”
Section: Efl University Students' Actual Use Of E-learningsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, attitude was found to be a significant predictor of students' actual usage of e-learning in English learning. This result is consistent with those of previous research on technology acceptance in language learning (Alfadda and Mahdi, 2021;Rafiee and Naghneh, 2021;Arif et al, 2022;Sulistiyo et al, 2022), demonstrating that factors of the technology acceptance model are the main factors influencing students' adoption of technology for language learning.…”
Section: Efl University Students' Actual Use Of E-learningsupporting
confidence: 92%
“…Also, this study found that PEoU significantly influences PU. In addition, this study showed that PEoU significantly influence Attitude, which is consistent with previous studies on TAM (Jiang et al, 2021;Sulistiyo et al, 2022).…”
Section: The Electronic Journal Of E-learning Volume 22 Issue 1 2024supporting
confidence: 92%
See 1 more Smart Citation
“…The Extended-TAM was suggested by some other scholars in that the factor of external variables is also considered to be a factor that affects users' acceptance and use of technology. Sulistiyo et al (2022) conducted research adopting TAM to investigate the TAM's determining factors toward the use of ICT tools for English learning. In this quantitative study, the TAM variables, namely Perceived Usefulness, Perceived Ease of Use, and Attitude, were entailed and expanded by three external factors, including Equipment, Motivation, and ICT Skills, to explore the pre-service teachers' attitudes toward ICT use for English learning.…”
Section: Tam Modelmentioning
confidence: 99%
“…The integration of Information and Communication Technology (ICT) has indeed significantly impacted ELL by transforming the traditional language learning domain (Parveen et al, 2023). Studies have shown that ICT plays a crucial role in improving language skills and motivating learners (Isnani, 2019;Sulistiyo et al, 2022). Teachers and students have generally shown positive perceptions towards the use of ICT in learning English, with students finding it more engaging and enjoyable (Gómez et al, 2018;Triassanti et al, 2022).…”
Section: Introductionmentioning
confidence: 99%